Interkulturelle Landeskunde im Bereich des Deutschen als Fremdsprache an kanadischen Hochschulen: Dokumentation einer Fallstudie am Department of German Studies der McGill University, Montreal, Quebec, Kanada - Mollinger, Karin (Université McGill, 1996)
Keywords: Allemands; Université McGill

McGill University’s racial exclusion of Japanese Canadians, 1943-1945 - Elsworthy, Tess (Université McGill, 2020)
Keywords: Japonais; Université McGill

Racialized social relations in higher education: Black student and faculty experiences of a Canadian university - Hampton, Rosalind (Université McGill, 2017)
Keywords: McGill Daily; McGill; James; Noirs; Université McGill

La langue de la libération / The Language of Liberation - Mills, Sean (Des actions parlantes. Aspects de la culture québécoise des années 1960 et 1970 / Actions that speaks. Aspects of Quebec Culture in the 1960s and 1970s, 2012)
Keywords: Anglophones; Francophones; Université McGill

Opération McGill français - Warren, Jean-Philippe (Une douce anarchie. Les années 68 au Québec, 2008)
Book Authors: _:n56851
Keywords: Anglophones; Associations étudiantes; Francophones; Université McGill

Rocke Robertson: surgeon and shepherd of change - Pound, Richard W. (McGill-Queen's University Press, 2008)
Keywords: Anglophones; Hôpitaux; Montreal General Hospital; Médecine; Université McGill; École de médecine

Champ culturel et espace montréalais (I): la vie culturelle à Montréal avant 1960 - Bellavance, Guy; Poirier, Christian (Histoire de Montréal et de sa région, 2012)
Keywords: Art association; Expositions; Musique; Musée McCord; Musées; Radio; Théâtre; Université McGill; Édition

Cultural Field and Montreal Space (I): Cultural Life in Montreal - Bellavance, Guy; Poirier, Christian (Montreal: The History of A North American City, 2018)
Keywords: Art association; Expositions; Musique; Musée McCord; Musées; Radio; Théâtre; Université McGill; Édition

Understanding the Patterns of Language Use of Chinese Children in a Montreal Community School - Curdt-Christiansen, Xiao Lan (Université McGill, 1999)
Keywords: Chinois; Langue; Étudiants

Ukrainian Community Life in Montreal: Social Planning Implications - Tokar, Ann M. (Université McGill, 1992)
Keywords: Ukrainiens

Transforming the Ideal: Visions and Revisions of Housing in a French-Canadian Community, 1942-1995 - Gilliland, Jason A. (Université McGill, 1996)
Keywords: Cité-Jardin du tricentenaire; Logement

The Young Men's Hebrew Association of Montreal: A Study of the Role of the Formal and Informal in an Ethnic Institution - Solomon, David N. (Université McGill, 1942)
Keywords: Juifs

The Well-Being of Kenyan-Canadian Parents and Youth Living in Mixed Families in Montreal - Williams, Alexandra (Université McGill, 2014)
Keywords: Africains; Famille

The Saint Patrick's Society of Montreal: Ethno-Religious Realignment in a Nineteenth-Century National Society - James, Kevin (Université McGill, 1997)
Keywords: Irlandais

The Role of The Gazette in Linguistic Group Relations in Quebec: A Contextual Approach - Ruvinsky, Ilene G. (Université McGill, 1984)
Keywords: Anglophones; Francophones; Montreal Gazette

The Refugee Youth Program in Montreal 1947-1952. A Descriptive and Analytical Study of the Integration of 40 Jewish Refugee Youths into the Montreal Community - Fischer, Greta; Switzer, Pearl (Université McGill, 1955)
Keywords: Enfants; Juifs

The Language Problem and School Board Reform on the Island of Montréal - Mackay, Murdo (Université McGill, 1987)
Keywords: Langue

The Greek Day School Socrates in Montreal: Its Development and Impact on Student Identity, Adjustment and Achievement - Bombas, Leonidas C. (Université McGill, 1988)
Keywords: Grecs

The Education of Italians in Montreal, 1895 to 1960 - Gadler, Yves Carmelo Luciano (Université McGill, 1994)
Keywords: Italiens

The Contributions of Montreal Holocaust Survivor Organizations to Jewish Communal Life - Giberovitch, Myra (Université McGill, 1988)
Keywords: Juifs

Sociolinguistic Features of Modern Greek as it is Spoken in Montreal - Maniakas, Theodoros (Université McGill, 1983)
Keywords: Grecs; Langue

Sri Lankan Women's Career Identity Evolution after Immigration to Montreal, Quebec, Canada - De Silva, Nilmini (Université McGill, 2010)
Keywords: Femmes; Sri Lankais; Travail

Shared Values, Different Paths: First-Generation Iranian Men's and Women's Perceptions of the Cultural Production of an "Educated Person" - Sadeghi, Shiva (Université McGill, 2004)
Keywords: Iraniens; Étudiants

Self-Identification Processes and their Reflection in the Language of Fourth-Wave Emigrants in Montreal - Migdissova, Svetlana (Université McGill, 2003)
Keywords: Langue; Russes

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Sankofa: Recovering Montreal’s Heterogeneous Black Print Serials - Williams, Dorothy W. (Université McGill, 2006)
Keywords: Noirs

Safeguarding Mother Tamil in Multicultural Quebec: Sri Lankan Legends, Canadian Myths, and the Politics of Culture - Brunger, Fern (Université McGill, 1994)
Keywords: Sri Lankais

Représentations culturelles et identité d'immigrants adultes de Montréal apprenant le français - Amireault, Valérie (Université McGill, 2007)
Keywords: Langue

Renegotiating Home and Identity: Experiences of Gujarati Immigrant Women in Suburban Montreal - Nair, Roopa (Université McGill, 1998)
Keywords: Femmes; Indiens

Private Rehabilitation in a Low Rent Area: Landlord-Tenant Relations and other Non-Market Factors - Duff, Huntly Douglas (Université McGill, 1973)
Keywords: Locataires; Logement; Portugais

Pressure Group Politics: Case Study of the St. Leonard Schools Crisis - Parisella, John E. (Université McGill, 1971)
Keywords: Italiens; Saint-Léonard (crise de)

L'insegnamento dell'italiano a Montreal verso il Duemila. Insegnamento e apprendimento al livello post-secondario in un contesto plurilingue - Picciano, Giovanna A. (Université McGill, 1997)
Keywords: Italiens; Langue

Die Geschichte des deutschsprachigen Theaters in Montreal von seinen Anfängen 1953 bis 1997 - Kremer, Johanna (Université McGill, 1998)
Keywords: Allemands; Théâtre

Using E-Government to Strengthen Montreal's Chinese Ethnic Economy - Han, Yang (Université McGill, 2006)
Keywords: Chinois; Commerce de détail; Internet

Dispersal and Concentration of the Vietnamese Canadians: A Montreal Case Study - Lavoie, Caroline (Université McGill, 1988)
Keywords: Vietnamiens

Britannique et Irlandaise: l'identité ethnique et démographique des Irlandais protestants et la formation d'une communauté à Montréal, 1834-1860 - Timbers, Wayne (Université McGill, 2001)
Keywords: Britanniques; Irlandais; Protestants

Collective Memory and Diasporic Articulations of Imagined Homes: Armenian Community Centres in Montreal - Manjikian, Lalai (Université McGill, 2005)
Keywords: Arméniens

The Kahnawake Iroquois and the Lower-Canadian Rebellions, 1837-1838 - Sossoyan, Matthieu (Université McGill, 1999)
Keywords: Autochtones; Iroquois; Rébellions

Immigrant Perceptions of Canadian schools: a Study of Greek Parents in Montréal - Shore, Bettina (Université McGill, 1979)
Keywords: Grecs

The Montreal Chinese Hospital 1918-1982: A Case Study of an Ethnic Institution - Ho, Kwong-Ming (Université McGill, 1984)
Keywords: Chinois; Hôpital chinois; Hôpitaux

The Role of the Black Community in Educating Blacks in Montreal, from 1910 to 1940, with Special Reference to Reverend Dr Charles Humphrey Este - Bertley, June A (Université McGill, 1982)
Keywords: Este; Charles Humphrey; Noirs

The Social Adjustment of British Immigrant Families in Verdun and Pointe-Saint-Charles - Davidson, Mary (Université McGill, 1933)
Keywords: Britanniques; Pointe-Saint-Charles; Quartiers; Verdun

Montreal Chinese Property Ownership and Occupational Change, 1881-1981 - Aiken, Rebecca Bruff (Université McGill, 1985)
Keywords: Chinois; Travail

The French and English Social Elites in Montreal - Ross, Eileen (Université McGill, 1941)
Keywords: Anglophones; Francophones

The Irish Migration to Montreal, 1847-1867 - Keep, George Rex (Université McGill, 1948)
Keywords: Irlandais

The Irish in Montreal, 1867-1896 - Cross, D. Suzanne (Université McGill, 1969)
Keywords: Irlandais

Occupational Mobility and Achievements of Post-War Chinese Immigrants in Montreal - Chiang, Frances Shiu-Ching (Université McGill, 1978)
Keywords: Chinois; Travail

The Slovakian Community in Montreal - Brown, Wilfrid Harold (Université McGill, 1927)
Keywords: Slovaques

The Occupational Adjustments of Montreal Negroes, 1941-1948 - Potter, Harold Herbert (Université McGill, 1949)
Keywords: Noirs

The Development and Social Adjustment of the Jewish Community in Montreal - Seidel, Judith (Université McGill, 1939)
Keywords: Juifs

The Montreal Negro Community - Israel, Wilfrid Emerson (Université McGill, 1928)
Keywords: Noirs

The Social Structure of the Italian and Ukrainian Communities in Montreal, 1935-1937 - Bayley, Charles M. (Université McGill, 1939)
Keywords: Italiens; Ukrainiens

The Attitudes of the Montreal Jewish Community toward French Nationalism and Separatism - Coleman, Romalis (Université McGill, 1967)
Keywords: Francophones; Juifs; Nationalisme

The Egyptians in Montreal: A New Color in the Canadian Ethnic Mosaïc - Wassef, Nadia Hanna (Université McGill, 1978)
Keywords: Égyptiens

The Economic and Social Adjustment of Slavic Immigrants in Canada with Special Reference to the Ukrainian of Montreal - Mamchur, Stephen (Université McGill, 1935)
Keywords: Ukrainiens

Ukrainian Bilingual Education in the Montreal Public School System, 1911-1945 - Melnyk, Iryna (Université McGill, 1987)
Keywords: Ukrainiens

The Occupational Adjustment of the British Immigrant in Montreal - Reynolds, Lloyd George (Université McGill, 1933)
Keywords: Britanniques

The Social Adjustment of Hungarian Refugees in Montréal - Gellert, Judith (Université McGill, 1964)
Keywords: Hongrois

"To Be Sold, a Negro Wench": Slave Ads of the Montreal Gazette, 1785-1805 - Extian-Babiuk, Tamara (Université McGill, 2006)
Keywords: Esclaves; Montreal Gazette; Noirs

The Economic Adjustment of North African Jewish Immigrants in Montreal - Moldofsky, Naomi (Université McGill, 1968)
Keywords: Juifs; Maghrébins

A Logic of Ethnicity: A Study of the Significance and Classification of Ethnic Identity among Montréal Portuguese - Fernandez, Ronald (Université McGill, 1977)
Keywords: Portugais

The Japanese in Montreal: Socio-Economic Integration and Ethnic Identification of an Immigrant Group - Keiko, Minai (Université McGill, 1977)
Keywords: Japonais

Effects of Migration on Alcohol Use: A Survey of Drinking Patterns, Attitudes and Alcohol-Related Problems among Ecuadorians in Ecuador and in Montreal - Vega Mansilla, Gustavo (Université McGill, 1982)
Keywords: Alcool; Équatoriens

A Study of the Academic Achievement and Personal and Social Adjustment of Jewish Moroccan Immigrant Students in the English High Schools of Montreal - Godfrey, Marvin Julian (Université McGill, 1970)
Keywords: Juifs; Maghrébins; Marocains

Montreal Anglophones: Social Distance and Emigration - Lange, Mélanie (Université McGill, 1985)
Keywords: Anglophones

Where Do I Belong? Narratives from the Lives of Iranians in Montreal - Dehghani Estarki, Mahdi (Université McGill, 2010)
Keywords: Iraniens

Examining the Overrepresentation of Black Males in the Young Offender System - Johnson, Druscilla (Université McGill, 2000)
Keywords: Délinquance; Noirs

"Doing it for the family": Educational Experiences of First-Generation Female Filipino Teens in Public Schools in Montreal - Pineda, Stephanie June (Université McGill, 2010)
Keywords: Philippins; Étudiants

Representing Twentieth Century Canadian colonial Identity: the Imperial Order Daughters of the Empire (IODE) - Pickles, Catherine Gillian (Université McGill, 1996)
Keywords: Britanniques; Femmes

Not a Place, but a Culture: The Cultivation of Iranian Subjectivity in Montreal - Hashemzadeh, Kianoosh (Université McGill, 2009)
Keywords: Iraniens

A Political Analysis of School Reorganization in Montreal - Fournier, Pierre (Université McGill, 1971)

Intégration et transnationalisme chez les Dominicains de Montréal - Dancause, Jacques-Luc (Université McGill, 2001)
Keywords: Caribéens

Cultural Sensitivity in the Context of Ethnic Polities: A Comparison of Two Families Service Agencies - Leung, Ho Hon (Université McGill, 2001)
Keywords: Chinois; Famille; Juifs

Independent Jewish Societies of Montreal. A Survey of the Nature and Extent of Philanthropic Programmes - 1949 - Shriar, Rupert (Université McGill, 1953)
Keywords: Juifs; Philanthropie

Political Economy, Transnationalism, and Identity: Students at the Montreal Hoshuko - Yoshida, Reiko (Université McGill, 2001)
Keywords: Japonais; Nationalisme

Life in an Urban Chassidic Community: Insulation and Proselytization. - Shaffir, William (Université McGill, 1972)
Keywords: Juifs

French and English in the Institutional Structure of Montreal: a Study for the Social and Economic Division of Labour - Jamieson, Stuart Marshall (Université McGill, 1938)
Keywords: Anglophones; Francophones

Reconstructing Tamil Masculinities: Kavati and Viratam among Sri Lankan Men in Montréal - Gross, Victoria (Université McGill, 2008)
Keywords: Sri Lankais

The Montreal Chassidic Community: Community Boundaries and the Maintenance of Ethnic Identity - Shaffir, William (Université McGill, 1969)
Keywords: Juifs

The Attitudes of Students of Greek Origin in a French-Language Learning Situation in a Québec Secondary School - Waite, Richard (Université McGill, 1991)
Keywords: Grecs; Langue; Étudiants

Identity, Place and Community: A Latin American Locale in Montreal - Occhipinti, Joseph (Université McGill, 1996)
Keywords: Latino-Américains

Young Second Language (L2) Learner's Meaning-Making: Consciousness, Collaboration, and Creativity (3Cs) - Kim, Mi Song (Université McGill, 2008)
Keywords: Coréens; Langue

Ethnicity as a Symbol System: a Theoretical Discussion Exemplified by Case Studies of Spaniards in Montreal - Fernandez, Ronald Louis (Université McGill, 1972)
Keywords: Espagnols

Secular and Parochial Education of Ashkenazi and Sephardi Jewish Children in Montreal: A Study in Ethnicity - Hirschberg, Jack Jacob (Université McGill, 1988)
Keywords: Enfants; Juifs

Ethnicity and Housing Adaptation: the Italians in Montreal - Fainella, John G. (Université McGill, 1986)
Keywords: Italiens; Logement

Crisis? What Crisis?: Anglophone Musicmaking in Montreal - Stahl, Geoff (Université McGill, 2003)
Keywords: Anglophones; Musique

Analyticity in Montreal Swedish - Gadelii, Karl Erland (Université McGill, 1988)
Keywords: Suédois

Analyse sociolinguistique de deux discours féministes - Helme, Mireille (Université McGill, 1984)
Keywords: Féminisme; Les Têtes de Pioche (journal)

Constructing Italian Ethnicity: A Comparative Study of Two Italian Language Newspapers in Australia and Canada, 1947-1957 - Iuliano, Susanna (Université McGill, 1994)
Keywords: Italiens

Chinese-Canadian Women in Montreal: Case Studies in the Importance of Education - Li, Sharon (Université McGill, 1995)
Keywords: Chinois; Femmes

Imagining Ethnicity. The Role of the Montreal Bangladeshi Press in Ethnic Cohesion - Ahmed, Shameem (Université McGill, 1997)
Keywords: Bengalis

There's No Place Like Home: Feminist Communities, Social Citizenship and (Un)Belonging in Montreal's Long Women's Movement, 1952-1992 - Ricci, Amanda (Université McGill, 2015)
Keywords: Anglophones; Autochtones; Femmes; Francophones; Féminisme; Haïtiens; Italiens; Noirs

Languages in Contact: Error Analysis of Italian Childrens' Compositions in a Multilingual Context - Samperi Mangan, Jacqueline (Université McGill, 1991)
Keywords: Enfants; Italiens; Langue

La letteratura dell'emigrazione italo-canadese di Montréal - Tedeschi, Antonio (Université McGill, 2000)
Keywords: Italiens

Jewish Supplementary Schooling in Montreal in the Latter Part of the Twentieth Century - Segal, Sima (Université McGill, 1991)
Keywords: Bureau des écoles protestantes; Juifs; Langue

Intra-Ethnic Differences of the Perceptions of Aged Italian Women in Receiving Care - Bonar, Rita Aguzzi (Université McGill, 1993)
Keywords: Femmes; Italiens

In the Shadow of the Mountain: A Historical Re-Evaluation of the 1988 Outremont Dispute - Herman, Dana (Université McGill, 2003)
Keywords: Juifs; Outremont

Italian Identity in Montreal: Issues of Intergenerational Ethnic Retention - De Martinis, Lucio (Université McGill, 2005)
Keywords: Italiens

In Search of Communal Identity: The Role of the Black Community in Identity Formation among Nigerian Youth - Ogbuagu, Buster C. (Université McGill, 2007)
Keywords: Nigériens; Noirs

Immigration, Ethnicity, and the Labour Market: The Chinese in Montreal - Pao-Mercier, Laura Yrien-Ha (Université McGill, 1982)
Keywords: Chinois; Travail

Hometown and Family Ties: The Lebanese-Syrians of Montreal, 1905-1950 - Moser, Diane (Université McGill, 1990)
Keywords: Libanais; Syriens

Hearing (Unheard) Voices: Aboriginal Experiences of Mental Health Policy in Montreal - Macdonald, Mary Ellen (Université McGill, 2003)
Keywords: Autochtones

Growing Up in Three Languages: Triliteracy Practices of Chinese Immigrant Children in Quebec - Curdt-Christiansen, Xiao Lan (Université McGill, 2003)
Keywords: Chinois; Langue

Gender, Race, and Power: the Chinese in Canada, 1920-1950 - Huang, Belinda (Université McGill, 1998)
Keywords: Chinois

Family, Paesani and Networks: Politics and Economy of Montreal Italians - Aramaki, Michiko (Université McGill, 1994)
Keywords: Italiens

The Emigration of Adam Smith's Ploughman: A Case Study of the Intellectual Culture of Scots Emigrants to Lower Canada, 1760-1850 - Gibson, Sarah Katherine (Université McGill, 2007)
Keywords: Écossais

The Irish in the Province of Canada in the Decade Leading to Confederation - Lyne, Daniel Colman (Université McGill, 1960)
Keywords: Irlandais

When Nationalisms Collide: Montreal's Italian Community and the St. Léonard Crisis, 1967-1969 - D'Andrea, Giuliano E. (Université McGill, 1989)
Keywords: Italiens; Saint-Léonard (crise de)

West Indian Associations in Montreal - Handelman, Don (Université McGill, 1964)
Keywords: Caribéens; Clubs

Race and beauty in Canada: print culture, retail, and the transnational flow of products, images and ideologies, 1700s to present - Thompson, Cheryl (Université McGill, 2014)
Keywords: Esclaves; Noirs

The Sattikka, the Turban and the Spices, the Cultural Landscape of a South Asian Neighbourhood: A Study on the Ethnic Diversity in Contemporary Montreal - Islam, Khadiza (Université McGill, 2016)
Keywords: Bengalis; Pakistanais; Parc-Extension (quartier); Quartiers; Sri Lankais

Imagining Sufism and Muslimness: the production of knowledge about Sufism and its power against political Islam in the United States, Canada, and Pakistan - Mercier-Dalphond, Geneviève (Université McGill, 2017)
Keywords: Musulmans

Bilinguefact your air: literary representations of French Canada, 1945-48 - Isler, Julia (Université McGill, 2017)
Keywords: Anglophones; Bilinguisme; Francophones; Roman

"Temple of my Heart": Understanding religious space in Montreal's Hindu Bangladeshi Community - Bhattacharjee, Aditya (Université McGill, 2017)
Keywords: Bengalis; Hindous

Blackness, exclusion, and the law in the history of Canada’s public schools, Ontario and Québec, 1850–present - Zellars, Rachel (Université McGill, 2017)
Keywords: Noirs

Imperialist Intent - Colonial Response : The Art Collection and Cultural Milieu of Lord Strathcona in Nineteenth-Century Montreal - Pierce, Alexandria (Université McGill, 2002)
Keywords: Smith; Donald

La poésie en langue des signes et ses usages à Montréal (1960-2017) - Daigneault, Catherine (Université McGill, 2018)
Keywords: Langue; Poésie; Sourds

Envisioning new futures: Portrait photographs of black Victorians in Montreal, 1861-1901 - Evoughlian, Sandra (Université McGill, 2018)
Keywords: Noirs; Notman; William; Photographie

Identity construction of Chinese immigrants: Exploring the processes of identity construction among Chinese immigrant parents and young adults in Montreal - Qian, Lingwei (Université McGill, 2016)
Keywords: Chinois; Quartier chinois; Quartiers

Reinforcing racial hierarchy through visual culture : black enslaved children in New France and early Quebec (1700-1834) - Trahan-Thomassin, Marilou (Université McGill, 2019)
Keywords: Enfants; Esclaves; Noirs; Peinture; Publicité

Elites and Scottishness in Montreal: identity, culture and the self in portait photography, 1860-1900 - Regimbald-Roy, Florence (Université McGill, 2021)
Keywords: Notman; William; Photographie; Écossais

Black slavery, historians and textbooks: A study of the representation of enslaved people of African descent in Quebec's historiography and history textbooks - Roethlisberger, Susanne (Université McGill, 2020)
Keywords: Africains; Esclaves; Histoire

A Fractured Identity: The 1980 Referendum and the Italians of Montreal - Pannunzio, Anthony (Université McGill, 2022)
Keywords: Indépendantisme; Italiens; Nationalisme; Référendums